2019
DOI: 10.32725/jab.2018.003
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt in athletes: hypoxia and doping - new crossroads

Abstract: Cobalt is an essential trace element that is known to mimic hypoxia and hypoxic training. Inorganic Co compounds are capable of Hypoxiainducible factor-1 (HIF-1) activation, resulting in up-regulation of gene expression including erythropoietin (Epo). Experimental studies have demonstrated that Co treatment may increase hypoxic tolerance of different tissues, improve muscle metabolism and exercise performance. Other mechanisms may also involve modulation of steroid hormone and iron metabolism. Based on these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 112 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…The available literature highlights the role of cobalt in fostering hypoxic tolerance by activating hypoxia-inducible factor 1 (HIF-1), which may partly elucidate its significance during physical activity [15]. It has been demonstrated that children with limited functional reserves often exhibit cobalt deficiency, further underscoring the importance of this element for overall bodily functions [16].…”
Section: Cobalt Exposure and Itsmentioning
confidence: 99%
“…The available literature highlights the role of cobalt in fostering hypoxic tolerance by activating hypoxia-inducible factor 1 (HIF-1), which may partly elucidate its significance during physical activity [15]. It has been demonstrated that children with limited functional reserves often exhibit cobalt deficiency, further underscoring the importance of this element for overall bodily functions [16].…”
Section: Cobalt Exposure and Itsmentioning
confidence: 99%
“…Co is an essential metal that possesses hypoxia-mimicking activity through the up-regulation of hypoxia-inducible factor 1-alpha (HIF-1α) signaling [ 179 ]. Co-based alloys are widely used for bone and joint implants [ 180 ], and therefore their impact on bone health is of particular interest.…”
Section: Cobalt (Co)mentioning
confidence: 99%